A 200-nm length TiO2 nanorod array with a diameter of 13 nm and areal density of 1100 µm−2 for efficient perovskite solar cells. Issue 15 (15th October 2017) - Xiao, Guannan; Shi, Chengwu; Li, Long; Zhang, Zhengguo; Ma, Chengfeng; Lv, Kai
Abstract: Rutile TiO2 nanorod arrays with lengths of 200 nm, 490 nm and 800 nm were prepared by a hydrothermal method using an aqueous grown solution of 38 mM titanium isopropoxide and 6 M hydrochloric acid at 170 °C for 75 min, 105 min and 115 min, respectively. CH3 NH3 PbI3−x Brx thin films were obtained by two-step sequential deposition using a 1.7 M PbI2 ·DMSO complex precursor solution and a 0.465 M isopropanol solution of a methylammonium halide mixture with a molar ratio of CH3 NH3 I/CH3 NH3 Br = 85/15. The influence of the microstructure of the TiO2 nanorod array on the charge separation at the perovskite/TiO2 interface and the photovoltaic performance of the corresponding solar cells were investigated. Perovskite solar cells based on a 200-nm length TiO2 nanorod array with a diameter of 13 nm and areal density of 1100 µm −2 exhibited the best photoelectric conversion efficiency (PCE) of 16.23%, with an open-circuit voltage ( V oc ) of 1.02 V, short-circuit photocurrent density ( J sc ) of 21.98 mA cm −2 and fill factor (FF) of 0.72, as well as an average PCE of 15.63 ± 0.60%, with a V oc of 1.00 ± 0.03 V, J sc of 21.80 ± 0.81 mA cm −2 and FF of 0.71 ± 0.02 under illumination of simulated AM 1.5 sunlight (100 mA cm −2 ).